Pengaruh Produk dan Harga Terhadap Keputusan Pembelian Beras Super Win di Toko Tina Salakan: The Influence Of Products and Prices on the Purchase Decision of Super Win Rice at Tina Salakan Shop - Anggita Putri; Arpan Kurubit (Jurnal Ilmiah Produktif, 2020)
This study was conducted to know the effect and significance of the influence of the product and price on purchasing decisions for awesome win rice products at the Tina Salakan shop. The number of samples in this study was 60 respondents. Based on the results of this study, the multiple regression equation Y = 2.285 + 0.378 X1 + 0.663 X2. The value of the correlation coefficient (R) is 0.397, and this value shows the close relationship between the independent variables consisting of Product (X1), Price (X2), and the dependent variable is Low Purchase Decision (Y). The value of the coefficient of determination (R^2) is 0.157, and this value shows the percentage of the contribution of the influence of the independent variable, namely Product (X1), Price (X2), on the dependent variable of Purchase Decision (Y) is 15.7%. Hypothesis testing shows that there is an influence between the independent variable product (X1) on the dependent variable on purchasing decisions (Y), indicated by the T-count value of the product (X1) of 3.149 > the T-table value of 1.672. and there is no influence between the independent variable price (X2) on the dependent variable purchasing decisions (Y) indicated by the value of T-count price (X2) of 0.442 < T-table value of 1.672.